If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x-3)+51(8x-66)=180
We move all terms to the left:
(3x-3)+51(8x-66)-(180)=0
We multiply parentheses
(3x-3)+408x-3366-180=0
We get rid of parentheses
3x+408x-3-3366-180=0
We add all the numbers together, and all the variables
411x-3549=0
We move all terms containing x to the left, all other terms to the right
411x=3549
x=3549/411
x=8+87/137
| 8s-22=3(3s+11)-s | | 18=s+9 | | 15m+3=48 | | 30=180(n-2) | | 12.50x+45=7.50x+75 | | 0.4x=6.2x+1.2 | | F(-7)=3x-2 | | x+-4=-20 | | g/29=10 | | 5(1/2x+2)=3*(x-2) | | 7-s=84 | | 6-4x=x+1-10x | | (3x-4)=(7x-54) | | 12h=540 | | 28=–2m | | 3u(u-1)(u-2)=0 | | p-50=-10 | | 20x9=10x9 | | 81=81-7t | | 10.x=80 | | Y=3x= | | z-306=143 | | 15c=+180 | | 660=6n | | y7,8;y=8 | | 10=t/4-2 | | 8(x=2)=-40 | | 7x=-170 | | 3x+6(x-5=48 | | 10xx=80 | | x+8+8x+1=180 | | u/9=13/11 |